2000
DOI: 10.1081/cbi-100102115
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Visual Detection Over the 24-Hour Period in Humans

Abstract: A circadian rhythm for visual sensitivity has been intensively assessed in animals. This rhythm may be due to the existence of a circadian clock in the mammalian eye, which could account for fluctuating sensitivity to light over the day in certain species. However, very few studies have been devoted to the human visual system. The present experiment was designed to assess a possible rhythm of visual sensitivity using a psychophysical method over the whole 24h period. Twelve subjects underwent visual detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…People detect changes in luminosity more easily in the evening, compared with the morning. 28 Detection of two separate sounds was also better in the evening. 2 Circadian variations have been documented in the perception of time.…”
Section: Circadian Variations In Performance Of Different Tasksmentioning
confidence: 86%
“…People detect changes in luminosity more easily in the evening, compared with the morning. 28 Detection of two separate sounds was also better in the evening. 2 Circadian variations have been documented in the perception of time.…”
Section: Circadian Variations In Performance Of Different Tasksmentioning
confidence: 86%
“…Earlier studies in humans showed a daily variation in retinal visual sensitivity, suggesting lower sensitivities in the early morning. [7][8][9] Besides a daily variation, a seasonal (circannual) variation might also be present. After all, exposure to light varies per season and prior light history affects light sensitivity.…”
Section: Methodsmentioning
confidence: 99%
“…6 Several researchers examined circadian rhythms in visual thresholds. [7][8][9]12,29 Although the confidence intervals were wide, retinal sensitivity seemed to be the lowest in the early morning. We found the lowest sensitivity directly after lunch and, in a subgroup of patients with early glaucoma, the highest sensitivity in the early morning.…”
Section: Time Of Daymentioning
confidence: 99%
“…Circadian changes of visual sensitivity have been previously described in humans. The studies have found increased threshold in the morning (13,27,28); the lowest threshold level has been detected at the beginning of the night (27,28) or in the second half of the night (29). The threshold has been lower at night than during the day (30).…”
Section: Discussionmentioning
confidence: 96%